Saddle avoidance of noise-induced transitions in multiscale systems - Reyk Börner; Ryan Deeley; Raphael Römer; Tobias Grafke; Valerio Lucarini; Ulrike Feudel (Physical Review Research)
In multistable dynamical systems driven by weak Gaussian noise, transitions between competing states are often assumed to pass via a saddle on the separating basin boundary. By contrast, we show that timescale separation can cause saddle avoidance in nongradient systems. Using toy models from neuroscience and ecology, we study cases where sample transitions deviate strongly from the instanton predicted by the Freidlin-Wentzell theory, even for weak finite noise. We attribute this to a flat quasipotential and present an approach based on the Onsager-Machlup action to aptly predict transition paths.